The development and validation of a numerical modelling approach for rotorcraft ditching - Horton, J.; Hawkes, G.; Neville, T. (My University, 2015)
In light of a number of instances of helicopters ditching, the safety and survivability of helicopters during and after ditching is undergoing increasing scrutiny by manufacturers, operators and regulators. This paper presents a summary of the numerical simulation approach that Frazer-Nash Consultancy Ltd has been working on to model both the initial ditching transient and the post-ditching stability of helicopters. The time domain simulation tool, HydroDyna, uses a combination of explicit calculations, empirical data and high fidelity Computational Fluid Dynamics simulation data to calculate the fluid loading on the fuselage and the resulting dynamics. Extensive validation has been successfully completed, culminating in the presentation of two case studies based on AgustaWestland's Lynx Wildcat and AW101. These case studies explored the ditching envelope of the Lynx Wildcat and the performance of flotation bags on the AW101. The case studies demonstrate the suitability of HydroDyna to model both the initial ditching transient and the postditching stability of helicopters as a flexible, repeatable and economic alternative to scale model tests.
Keywords: Safety